Internal Carotid Artery Rupture during Mechanical Thrombectomy of Tandem Occlusion - Ariharan K.; Sharath Kumar G.G; Somasree Manna (Journal of Clinical Interventional Radiology ISVIR)
Mechanical thrombectomy of tandem occlusion involving the internal carotid artery (ICA) is effective but complex. We discuss ICA rupture during thrombectomy of a tandem ICA occlusion. After crossing the ICA origin, manual angiography in the closed segment between proximal severe stenosis and distal thrombus leads to ICA rupture. The combination of high pressure created in a closed segment and weak structural points can lead to the rupture. The rupture can happen at the intradural segment of the ICA or an aneurysm. This complication may be avoided by an antegrade approach to tandem occlusions, low-flow microcatheter injections, and common carotid artery injections.